On-farm Research Trials in Mushroom Farming: Technology assessment and constraint based recommendations - Shirur, Mahantesh; VED PRAKASH, SHARMA; UPADHYAY, RC; AHLAWAT, OP; KUMAR, SATISH; KAMAL, SHWET; YADAV, AJAY SINGH; CHINNARA, NIRANJAN (Mushroom Research, 2018)
On farm research (OFR) is the most reliable tool to test the technologies for their testing, validation and promotion. Such OFR trials provide an excellent opportunity to compare the performance of the proposed system and farmer’s traditional practice in a reliable way. The objectives of the research were to test the technologies, identify the constraints experienced by the farmers and to elicit the suggestions to overcome them. Five technologies were tested and all the five technologies were found to give better result over the existing ones with varying degree of success. The technologies in mushroom farming will prove significant in raising the farmersâ€™ income. Implementation constraints, climate and crop management practices demanded further precision. The quality of shiitake mushrooms needs to be addressed through genetic improvement studies. The non-technological problems such as marketing and value addition also surfaced after the trails. The OFR trials helped in promoting the diverse mushrooms in non-traditional areas to expand the availability of edible mushrooms to the consumers.